PBC, an easy and efficient strategy for high-throughput protein C-terminome profiling - Zhai, Linhui; Wang, Le; Hu, Hao; Liu, Quan; Lee, Sangkyu; Tan, Minjia; Zhang, Yinan (Frontiers in Cell and Developmental Biology, 2022)
High-throughput profiling of protein C-termini is still a challenging task. Proteomics provides a powerful technology for systematic and high-throughput study of protein C-termini.. Various C-terminal peptide enrichment strategies based on chemical derivatization and chromatography separation have been reported. However, they are still costly and time-consuming, with low enrichment efficiency for C-terminal peptides. In this study, by taking advantage of the high reaction selectivity of 2-pyridinecarboxaldehyde (2-PCA) with α-amino group on peptide N-terminus and high affinity between biotin and streptavidin, we developed a 2-PCA and biotin-labeling based C-terminomic (PBC) strategy for high-efficiency and high-throughput analysis of protein C-terminome. Triplicates of PBC experiments identified a total of 1,975 C-terminal peptides corresponding to 1,190 proteins from 293T cell line, which is 180% higher than the highest reported number of C-terminal peptides identified from mammalian cells by chemical derivatization-based C-terminomics study. The enrichment efficiency (68%) is the highest among the C-terminomics methods currently reported. Besides, we uncovered 50 proteins with truncated C-termini which were significantly enriched in extracellular exosome, vesicle and ribosome by bioinformatics analysis, suggesting PBC as a powerful tool for protein C-terminal degradomics investigation. In conclusion, the PBC strategy would benefit high-efficiency and high-throughput profiling of protein C-terminome.